Hubungan Vaksinasi Rotavirus dengan Kejadian Diare pada Bayi di Wilayah Kerja UPT Puskesmas Sei Panas Kota Batam Tahun 2024 - Arnisona Tumiar Br Sinaga; Nelli Roza; Huzaima Huzaima (Pusat riset dan Inovasi Nasional, 2025)
Diarrhea is a leading cause of morbidity and mortality in children under five, particularly in developing countries like Indonesia. To reduce the incidence of diarrhea, the government has implemented a policy to prevent it by administering rotavirus vaccination. To determine the relationship between rotavirus vaccination and the incidence of diarrhea in infants in Sadai sub-district, the working area of UPT Puskesmas Sei Panas, Batam City in 2024. This study was a quantitative study with a cross-sectional approach to 72 infants who received rotavirus vaccination.The implementation time starts on October 23 to November 06, 2024. Sampling using cluster random sampling technique. Measurement tools using questionnaires and observation sheets. Analysis of the data used is the chi square test. The study obtained rotavirus vaccination as many as 40 infants (55.6%), the incidence of moderate diarrhea as many as 37 infants (51.4%). Chi-Square test results showed the value of p value = 2.167. Because of the value (p value 2.167 > 0.05), this relationship is not statistically significant. There is no significant relationship between rotavirus vaccination and the incidence of diarrhea in infants in Sadai Village working area of UPT Puskesmas Sei Panas Batam City in 2024.